SOSIALISASI MESIN PENGERING CENGKEH DI DESA BUTTU BARTONG KABUPATEN SIMALUNGUN - Jhon Sufriadi Purba; Maren Sius Girsang (Abdi Jurnal Publikasi, 2026)
Historically, cloves were one of the main spices that drove international trade routes and the arrival of Europeans to the Indonesian archipelago. Cloves remain a crucial commodity today, particularly for the clove cigarette, pharmaceutical, food, beverage, and essential oil industries. Drying cloves is a crucial stage in the post-harvest process, aimed at reducing water content and improving product quality. This clove drying machine socialization aims to accelerate clove production in Buttu Bartong village, addressing the energy needs of clove drying machines with various heating elements: electric, gas, and biomass heaters. The method used is socialization of clove drying machines with various heating elements to accelerate clove harvest production in Buttu Bartong village. Electric heaters provide more stable temperature control, while gas heaters show lower operational costs. This socialization is expected to provide recommendations regarding optimal drying systems, which are not only energy efficient but also economical, thus supporting the sustainability of optimal clove processing production.